Branding Strategy for Entry into New Latin American Markets An Institutional and Cultural Approach; Bimbo Case - Jose Vargas-Hernandez; Elsa Patricia Orozco Quijano; Raquel de Guadalupe Flores Murguia (Universitas Kuningan, 2018)
The main objective of this article is to analyze theories of institutions and culture approach, and relevant aspects that could influence entrepreneurs in entering new Latin markets. Using a qualitative research methodology, this research analyzed the application of branding strategies used by “Bimbo” one of the most influential companies in the baking industry worldwide, to enter new Latin American markets including Argentina, Brazil and Peru. Graphic forms of some banding strategies are revised and analyzed in this paper as well as the branding process. This paper concludes by deliberating the successes of Bimbo in entering new markets. It discusses all major success factors identified in the strategy in which included culture, consumption habits, customs, values and laws; fundamental aspects to be considered in entering a new Latin market.